Analysis of the preforming behaviour of the braided and woven flax/polyamide fabrics. (September 2016) - Jacquot, Pierre-Baptiste; Wang, Peng; Soulat, Damien; Legrand, Xavier
Natural flax fibres have been extensively recognized by automotive industries to reduce the weight of vehicles and obtain recyclable composite parts. Most of composite parts are produced by using resin transfer moulding or thermoforming processes. As the first step of these two composite manufacturing processes, the preforming is quite important. Braided and woven fabrics are widely used as textile reinforcements to manufacture the advanced composite parts. But few research works concern the preforming of the reinforcements based on natural fibres and also there is no analysis of dry braided fabrics forming. In the present work, the studies of formability behaviour of braided and woven fabrics made of the same flax/polyamide 12 commingled yarns are performed. Furthermore, an experimental comparison between the preforming behaviour of braided and woven flax/polyamide fabrics is investigated under identical preforming conditions. The different formability behaviour and the defects developed during preforming stage are analysed. First results obtained on hemispherical shape show a higher deformability for the braided reinforcements, which can generate some forming defects, in particular buckles.